Enhanced Electrochemical Performance of Dual-Ion Batteries with T-Nb2O5/Nitrogen-Doped Three-Dimensional Porous Carbon Composites - Chen Qi; Duo Ying; Cheng Ma; Wenming Qiao; Jitong Wang; Licheng Ling (Molecules)
Niobium pentoxide (T-Nb2O5) is a promising anode material for dual-ion batteries due to its high lithium capacity and fast ion storage and release mechanism. However, T-Nb2O5 suffers from the disadvantages of poor electrical conductivity and fast cycling capacity decay. Herein, a nitrogen-doped three-dimensional porous carbon (RMF) was prepared for loading niobium pentoxide to construct a composite system with excellent electrochemical performance. The obtained T-Nb2O5/RMF composites have a well-developed pore structure and a high specific surface area of 1568.5 m2 g−1, which could effectively increase the contact area between the material and electrolyte, improving the electrode reaction and lithium-ion transfer diffusion. Nitrogen doping increased surface polarity, creating more active sites and accelerating the electrode reaction rate. The introduction of T-Nb2O5 imparted high power density and excellent cycling stability to the battery. The composites exhibited good electrochemical performance when used as dual-ion battery anode, with a stable cycle life of 207.2 mA h g−1 at 1 A g−1 current density after 650 cycles and great rate performance of 181.5 mA h g−1 at 5A g−1 was also obtained. This work provides the possibility for applying T-Nb2O5/RMF as an anode for a high-performance dual-ion battery.